2021
DOI: 10.1016/j.afjem.2021.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital care for traumatic spinal cord injury by first responders in 8 sub-Saharan African countries and 6 other low- and middle-income countries: A scoping review

Abstract: Introduction Traumatic spinal cord injury (TSCI) constitutes a considerable portion of the global injury burden, disproportionately affecting low- and middle-income countries (LMICs). Prehospital care can address TSCI morbidity and mortality, but emergency medical services are lacking in LMICs. The current standard of prehospital care for TSCI in sub-Saharan Africa and other LMICs is unknown. Methods This review sought to describe the state of training and resources for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Similar to previous scoping reviews on airway management and spinal cord injury, 52,53 an accessibility challenge to prehospital HM in LMICs persists. In high‐income countries (HICs), effective bioengineered hemostatic agents, such as RickClot Combat Gauze (QCG), Tranexamic Acid (TXA), and RevXSTAT (XSTAT), are first‐line agents for life‐threatening bleeds not controlled by tourniquets 54 .…”
Section: Discussionmentioning
confidence: 68%
“…Similar to previous scoping reviews on airway management and spinal cord injury, 52,53 an accessibility challenge to prehospital HM in LMICs persists. In high‐income countries (HICs), effective bioengineered hemostatic agents, such as RickClot Combat Gauze (QCG), Tranexamic Acid (TXA), and RevXSTAT (XSTAT), are first‐line agents for life‐threatening bleeds not controlled by tourniquets 54 .…”
Section: Discussionmentioning
confidence: 68%
“…Data collected from studies focused on: authors, title, publication year, study setting and World Bank income country income classification, occupation of individuals providing prehospital AM care and the level of training received (LFR, BLS, PHTLS, ALS), training duration for care providers, curricular elements involved in training, equipment used in the provision of prehospital care, frequency of reported interventions, frequency of reported adverse events, clinical impact of prehospital interventions taken, and the number trained or surveyed. Interventions taken were also further classified as basic AM or advanced AM following basic and advanced life support protocol [22][23][24] (Table 2). EMS personnel are trained as professional first responders who transport patients from an injury scene to a clinical setting for definitive care as their full-time or part-time occupation.…”
Section: Data Collectionmentioning
confidence: 99%
“…[ 5 ] The global burden of acute TSCI, constitutes a considerable portion of the global injury burden as published by the 2019 Global Burden of Disease study group. [ 5 8 ] Although the study revealed that from 1990 to 2016, there was no significant change in the age standardised incidence or prevalence of TSCI, the population of people living with the consequences of TSCI is expected to rise, due to population growth in the near future, leading to an increase in the demand for specialised care of patients with this injury. [ 5 ] The prevalence and incidence of TSCI might not have changed much over time, however, there are marked variations in the incidence, prevalence and other clinical characteristics of this injury across, and within different countries and regions of the world.…”
Section: Introductionmentioning
confidence: 99%